Digital-Based MSME Program Marketing Communication Adaptation - Rizky Al-Huda; AlqiHernanda Gymnastiar; Fatria Adipati Ramadhan; Khaerudin Imawan; Dedet Erawati (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study analyzes the digital marketing adaptation of SMEs through social media, with a focus on strategies, impacts, and direct interactions with consumers. Qualitative descriptive research method was employed to gather data from relevant journals. The findings indicate that digital marketing enables SMEs to expand market reach and strengthen relationships with consumers through two-way interaction. Relevant and creative content strategies were found to be crucial in standing out in the information-dense online environment. Positive impacts on SME product sales were also observed, particularly through social media platforms such as Instagram and TikTok.Direct interaction with consumers via social media platforms strengthens relationships and allows brands to listen to consumer feedback directly. In conclusion, digital marketing adaptation through social media is essential in developing SME products and expanding their market share.